Numbers - Sirett, Dawn; Jennings, Charlotte; Palastanga, Victoria (London dorling kindersley, 2012)
Let's look for a cake with 1 candle.Let's point to a number 4 on a truck.Let's find 10 pink pages. Packed with pictures, this fun-filled number book is perfect for children and adults to share together.Just look and find!
Arithmetic notions
Available edition 2015 in Misr Public Library - Giza branch
Available edition 2015 in Misr Public Library - Mobile Library
Keywords: Mathematics